PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN RUMAH MAKAN SUBULUSSALAM - Gunawan Gunawan; T Andi Roza (SI-MEN, 2021)
The purpose of study was to determine the quality of service and product quality simultaneously on consumer satisfaction at Subulussalam Restaurant, with a total sample of 100 people. Respondents were successfully collected and analyzed by using multiple linear regression method through SPSS (Statistical Package for Social Sciences). The results showed that service quality partially had a significant effect on consumer satisfaction at Subulussalam Restaurant t-count value was greater than t-table, t-count (4.210) > t-table (1.984). Product quality partially has a significant effect on consumer satisfaction at Subulussalam Restaurant t-count value is greater than t-table, t-count (5,129) > t-table (1,984). Service quality, product quality simultaneously affects consumer satisfaction at Subulussalam Restaurant F-count value is greater than F table, F-count (7.118) > t-table (3.09)